Clinical and Dermatoscopic Features of Seborrheic Keratoses According to Skin Types: A Retrospective Study - Sadia Ammad; Gaetano Licata; Gabriella Brancaccio; Elvira Moscarella; Giuseppe Argenziano (Mattioli1885, 2023)
Introduction: Seborrheic keratoses (SK), are very common benign skin lesions, which may increase in number and size with age. Objective: The aim of the study was to assess any differences seen in seborrheic keratoses in relation to different skin types (ST) and lesion location. Methods: This was a retrospective observational study of 10-months period, based on dermoscopic images of seborrheic keratoses and patient history recorded in database. Patients were categorized according to their age, sex, skin type, and location of SK. Results: The frequency of SK remained high on the back for skin type 1, 2, 3 and 4. This same trend was also seen on the face and chest.  In skin type 3 we saw a reversal of distribution of SK, the highest frequency remained on the back, and this was followed by the chest rather than the face. In skin type 5 and 6, the nature of the distribution of SK was more facial, Conclusions:  In summary our study shows that SK are more commonly seen in males than in females, they tend to dominate in sun exposed sites especially the back and the face. Both the smaller and larger sized SK dominated in ST 1 and 2. The lighter to darker shades of colour seen in seborrheic keratoses varied in accordance with the skin type, with lighter coloured SK being seen more in lighter skin types as compared to darker skin types, whereas bluish coloured SK were seen in all skin types except ST 1.